The Effectiveness of PAlliative Split COurse RAdiotherapy (PASCORA) Regimen in Non-metastatic Head and Neck Cancer Patients who are Treated with Palliative Intent- A Retrospective Single Centre Study - Velu, Umesh; Shetty, Preethi S; Singh, Anshul; Salins, Shirley; Sharan, Krishna (Asian Pacific Journal of Cancer Biology, 2022)
Introduction: We at our centre practice a PAlliative Split COurse RAdiotherapy (PASCORA) of 22.5Gy in 5 fractions followed by a gap of 4 weeks and then again repeat 22.5Gy in 5 fractions for locally advanced squamous cell carcinoma patients treated with a palliative intent. Aim was t0 assess the symptomatic relief at 3 months following PASCORA regimen. Materials & Methods: 49 Patients with LAHNSCC between January 2014 to January 2021, planned for PASCORA regimen were evaluated. Symptomatic relief was assessed on an objective scale. OS was determined using Kaplan Meir survival curves. Results: Median age was 61 years, multiple comorbidities (37%) were the most commonly documented reason for these patients being treated with a palliative intent. 25% of our patients had an excellent symptomatic relief, 26% of our patients had a good symptomatic relief and 31% had a partial relief. Median OS was 38 months in patients who had an excellent symptomatic relief and 3-8 months in patients with no or partial symptomatic relief ( p value=0.000) 6% of our patients had Grade 3 /4 RTOG toxicity. Conclusion: PASCORA regimen offers a good symptomatic relief with good local control rates and acceptable level of toxicity and comparable OS.